Swim Training Attenuates Inflammation and Improves Insulin Sensitivity in Mice Fed with a High-Fat Diet - Guangzeng Zhang; Pengfei Yu; Xiaomeng Liu (International Journal of Endocrinology)
Exercise could afford multiple beneficial effects on obesity-related metabolic disorders. To address this issue, C57BL/6J mice were used to investigate the effects of 13 weeks of swim training on HFD-induced obesity and related insulin resistance and inflammation. Our results show that swim training can significantly prevent HFD-induced weight gain and increase resting energy expenditure without affecting food intake. The insulin sensitivity was enhanced in the HFD + swim group than in the HFD + sedentary group. Moreover, swim training considerably decreased serum LPS content and downregulates epididymis white adipose tissue (eWAT) expression of the inflammatory mediator Tnf-α, Il-6, and Mcp-1. In summary, 13 weeks of swim training could reverse HFD-induced metabolic disorders including insulin resistance and inflammation.